2017
DOI: 10.1002/jso.24692
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of postmastectomy reconstruction: A comparison of two staged implant reconstruction using tissue expander and acellular dermal matrix with abdominal‐based perforator free flaps

Abstract: DIEP flap breast reconstruction incurs lower costs compared to TE/I + ADM. These costs are lower at baseline and when additional costs from pooled complications are incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
(72 reference statements)
0
19
0
1
Order By: Relevance
“…Therefore, no score was assigned in these criteria. The 2 comparative cost analysis studies by Tran et al 29 and Matros et al 30 both scored an overall "low risk of bias." The prospective cohort study of Lagares-Borrego et al 1 and the retrospective observational cohort study of Ricci et al 31 scored a high risk of bias on 1 criterion (1 of 14 criteria) as well as the study of Pelletier et al (1 of 7 criteria).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, no score was assigned in these criteria. The 2 comparative cost analysis studies by Tran et al 29 and Matros et al 30 both scored an overall "low risk of bias." The prospective cohort study of Lagares-Borrego et al 1 and the retrospective observational cohort study of Ricci et al 31 scored a high risk of bias on 1 criterion (1 of 14 criteria) as well as the study of Pelletier et al (1 of 7 criteria).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…To assess the quality of the cost analysis studies, the short checklist by Drummond et al was used ( Table 5). The study of Tran et al 29 as well as the study of Matros et al had an overall score of "low risk of bias." 30…”
Section: Cost Analysis Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional cost is incurred if breast reconstruction is associated with Acellular Dermal Matrix (ADM). 13,14 ADM is frequently used in expander based breast reconstruction because facilitates complete implant coverage providing support to the inferior-lateral pole of the implant. ADM gives a faster tissue expansion, a reduction of post-operative pain and an improvement of the aesthetic outcome, 15,16 reducing concerns for complications such as rippling and malposition.…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, Cost Analysis of Postmastectomy Reconstruction: A Comparison of Two Staged Implant Reconstruction using Tissue Expander and Acellular Dermal Matrix with Abdominal Based Perforator Free Flaps by Tran et al the authors concluded that DIEP flap reconstruction incurred lower costs compared to tissue expander − implant − acellular dermal matrix (TE‐I‐ADM) reconstruction. The calculations for the study were based on Medicare reimbursement costs for each procedure that also included the costs of the associated complications.…”
mentioning
confidence: 99%